Alopecia Areata: A syphilitic miasmatic expression successfully treated with Homoeopathy- A case Report - DR. MITAL N. KACHA; DR. HEENA K. RAWAL (The Bioscan, 2025)
The following case report is alopecia areata in 23 years old male who was treated successfully with individualised homoeopathic medicine within 6 months of treatment. Syphilinum was prescribed as a constitutional remedy on the basis of totality of symptoms and after the repertorisation. Homoeopathic medicines have wonderful results in such type of cases, where the modern medicines have very less effective treatment. KEYWORDS Alopecia Areata, Syphinium, Syphilitic miasms, Homoeopathy, Miasmatic Analysis, Case report.